Peran Pos Kesehatan Pesantren (Poskestren) Terhadap Upaya Promotif, Preventif dan Kuratif Karies Gigi Santri Pondok Pesantren Roudhotul Jannah Makassar - Lesmana, Hans; Supriatna, Agus; Priyambodo, Ardian; Wahju Purwaningsih, Roosi; Nuraziziah, Nuraziziah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Dental caries and periodontal disease are the most common diseases in the oral cavity. Dental caries can occur in everyone regardless of age including adolescents. Maintenance of children's oral health, the role of parents is very important. However, for adolescents who live in boarding schools, of course, their interaction with parents will be reduced, so that all forms of teaching and education are reduced, so this is where the importance of the role of boarding school caregivers in fostering their students not only on the spiritual side but also in terms of maintaining health, given their role as foster parents for their students. This study is an analytical observational study with a cross sectional approach, involving the entire population of 51 people as a sample. Data were collected through guided interviews using a questionnaire. The results of this study showed that Poskestren did not play an active role in maintaining the oral health of students. The conclusion of this study shows that Poskestren plays a less active role in prevention efforts (promotive and preventive) and plays a less role in handling various oral disease problems, especially the incidence of caries (Curative) experienced by students at the Roudhotul Jannah Islamic Boarding School Makassar.